17.7k views
5 votes
Help please i need helpp!!!

Help please i need helpp!!!-example-1

1 Answer

5 votes

Answer:

The answer to your question is:

22.- P1 ( -4, -7) P2 (0, 3)

23.- P1 ( 4, 9) P2 (-4, -7)

Explanation:

22.-

y = x - 3

y = -x² + 9

Solve it by substitution

x - 3 = -x² + 9

x² + x - 3 - 9 = 0

x² + x - 12 = 0

( x + 4)(x - 3) = 0

x1 = - 4 x2 = 3

Finally

y1 = -4 - 3 x2 = 3 - 3

y 1 = -7 x2 = 0

P1 ( -4, -7) P2 (0, 3)

23.- y = 2x + 1

y = x² + 2x - 15

Substitution

2x + 1 = x² + 2x - 15

x² + 2x - 2x - 15 - 1 = 0

x² = 16

x = ± 4

x1 = 4 x2 = -4

y1 = 2(4) + 1 y2 = 2(-4) + 1

y1 = 9 y2 = -7

P1 ( 4, 9) P2 (-4, -7)